Bureaucratic discretion, social equity, and the administrative legitimacy dilemma: Complications of new public service - Rivera, Jason D. and Knox, Claire Connolly (Public Administration Review)
Bureaucratic discretion continues to be one of a public administrator's primary powers while at the same time being one of their most controversial. Used in a positive way, bureaucratic discretion can enhance social equity; however, this practice can create administrative legitimacy dilemmas. As such, this paper conceptually discusses the theoretical position of public administrators that contributes to their engagement in legitimacy dilemmas, which is further complicated by the tenets of New Public Service. We argue that if public administrators are engaged in authentic interactions with the public and use their discretion to reflect the interests of the public, then they are engaged in truly democratic governance. We place this argument in the context of achieving social equity and highlight an avoided question in public administration. Finally, recommendations for future research are offered as a means progressing the social equity agenda in public administration.- Reproduced